Cardiovascular Perceived Exertion and Blood Lactate Response afterBadminton Matches - Manhal Nabeel Boya Boya (University of Basrah, 2021)
Badminton is the fastest racket game with action of short duration and high intensity.  Purpose: to measure and compare blood lactate concentration, PRE, heart rate and blood pressure before and after repeated badminton matches. Method: Six national ranked players (age = 22.6 ± 5.3 years; height = 172.5 ± 3.2 cm, weight = 66.1 ± 5.3 kg) played four badminton matches in raw with recovery period of 30 minutes in which Heart Rate, Blood pressure and RPE were measured before and immediately after the end ofeach match. Additionally, blood lactate concentration was measured before and after 5 min from the end of the match. Result: the study indicates that blood lactate concentration and RPE were higher in the fourth match comparing to others with significant differences among them for both before F3, 15= 20.08, P=0.000, F3, 15= 14.80, P=0.000, and after the end of the matches F3, 15= 16.48, P=0.000. F3, 15= 13.71, P=0.000, respectively. No significant differences for heart rate and blood pressure were found. Conclusion: the repetitive badminton matches exerted high cardiovascular and psychophysiological stress on the players. Reconsidering the given recovery time and the number of games allowed per day during national and international tournaments is highly recommended.